Analysis Of Student Errors In Solving Intgral Questions For Grade XII IPS 1 At MAS YMPI Tanjungbalai - Irmayanti Mangunsong (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research has a purpose to analyze students' errors in solving problems combined to integral calculus in Grade XII IPS 1. This is a descriptive study with a qualitative approach. The research subjects has 30 students and 3 mathematics teachers. The instruments used are tests (reliability coefficient V=0.76) and questionnaires (reliability coefficient V=0.68). Data is collected with four methods: 1) students are asked to complete a descriptive test on integral calculus in 5 questions on a worksheet, 2) collecting and analyzing some of the students' answers, 3) interviewing with some students who face difficulties, and 4) interviewing teachers. The research instruments used include a descriptive test on integral calculus, interview worksheets for students and mathematics teachers. Data analysis is carried out in three stages: 1) identifying and categorizing students' errors in answering the questions, 2) analyzing students' errors, and 3) examining the correlation between students' test results and the results of interviews with students and teachers. The results of the study show that out of 30 students who took the test, 12 or 40% of the students did not meet the passing criteria (KKM = 70), 7 or 23.3% of the students made errors in understanding basic integral concepts, 12 or 40% of the students made errors in applying principles, and 13 or 43.3% of the students made errors in solving problems in text questions. From the questionnaire and interview results, it has been found that 16 or 53.3% of the students are mostly influenced by internal factors, and 11 or 36.6% of the students are mostly  influenced by external factors